2016
DOI: 10.1074/jbc.m115.708453
|View full text |Cite
|
Sign up to set email alerts
|

PqsBC, a Condensing Enzyme in the Biosynthesis of the Pseudomonas aeruginosa Quinolone Signal

Abstract: Pseudomonas aeruginosa produces a number of alkylquinolone-type secondary metabolites best known for their antimicrobial effects and involvement in cell-cell communication. In the alkylquinolone biosynthetic pathway, the β-ketoacyl-(acyl carrier protein) synthase III (FabH)-like enzyme PqsBC catalyzes the condensation of octanoyl-coenzyme A and 2-aminobenzoylacetate (2-ABA) to form the signal molecule 2-heptyl-4(1H)-quinolone. PqsBC, a potential drug target, is unique for its heterodimeric arrangement and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 56 publications
2
69
0
Order By: Relevance
“…PqsA converts anthranilic acid to anthraniloyl-CoA that is condensed with malonyl-CoA to form 2-aminobenzoylacetyl-CoA (2-ABA-CoA) in a reaction catalysed by PqsD [15,16]. The thioesterase activity of PqsE converts 2-ABA-CoA into 2-aminobenzoylacetate (2-ABA) [17]; HHQ is formed through the condensation of octanoyl-coenzyme A and 2-ABA via the PqsBC heterodimer [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…PqsA converts anthranilic acid to anthraniloyl-CoA that is condensed with malonyl-CoA to form 2-aminobenzoylacetyl-CoA (2-ABA-CoA) in a reaction catalysed by PqsD [15,16]. The thioesterase activity of PqsE converts 2-ABA-CoA into 2-aminobenzoylacetate (2-ABA) [17]; HHQ is formed through the condensation of octanoyl-coenzyme A and 2-ABA via the PqsBC heterodimer [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Owing to its instability, it can spontaneously decompose into 2‐aminoacetophenone (2‐AA) by the loss of CO 2 or by undergoing intramolecular cyclization into 2,4‐dihydroxyquinoline (DHQ) . In the main biosynthetic route to HHQ, however, the heterodimeric PqsBC complex (EC 2.3.1.180) transfers 2‐ABA onto octanoate to synthesize HHQ in a decarboxylative Claisen condensation after an acyl‐enzyme intermediate between the active‐site cysteine (C129) of PqsC and octanoyl‐CoA is formed . In a final step, HHQ is hydroxylated at the C3 position by the monooxygenase PqsH .…”
Section: Introductionmentioning
confidence: 99%
“…Because the pqs system is unique to P. aeruginosa and has a central role in virulence, it might present an attractive target for new pathoblocker approaches. To this end, structural information provides important insight into the ligand‐binding properties of proteins, and since the discovery of the pqs system crystal structures of nearly all PQS biosynthetic proteins, with the exceptions of PqsA and PqsH, and of the ligand‐binding domain of the HHQ/PQS‐responsive transcription factor MvfR have become available . PqsH, however, seems to be an unpromising drug target, because it has been demonstrated that a P. aeruginosa PA14 pqsH mutant that is unable to transform HHQ into PQS exhibits virulence similar to that of the wild‐type strain .…”
Section: Introductionmentioning
confidence: 99%